Peningkatan Literasi dan Numerasi Melalui Program Asistensi Mengajar di SMP Negeri 2 Waingapu - Chening Nonci Lewi; Richviera Grace Widyarti; Susanti Kahi Leba; Yoin Meissy Matulessy; Kevin Andrea Tamaela; Anita Tamu Ina (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
The implementation of teaching assistance from the Ministry of Education and Culture of the Republic of Indonesia provides an opportunity for students to increase their insight and gain experience in helping the teaching and learning process in educational units. The implementation method at the Partner School, namely SMP Negeri 2 Waingapu, has several stages, namely observation, interview implementation, and evaluation. The rograms implemented are academic activities including literacy (Creating a knowledge tree), numeracy (Creating a multiplication control pocket book, non-academic activities (biology and mathematics learning media exhibition) and library space arrangement. The results achieved from creating a knowledge tree through literacy produce structured understanding, facilitate information organization, and improve critical thinking skills. The results of numeracy through the creation of a multiplication control pocket book are an increase in the ability to calculate quickly and accurately, and make it easier for students to remember and master multiplication tables in a practical and efficient way. The results of the Biology and Mathematics learning media exhibition are an increase in student understanding through interactive visualization, which makes it easier for them to understand complex concepts in both subjects. The results of the library space arrangement are the creation of a more organized, comfortable, and efficient space, which supports the comfort of visitors in accessing information sources.